Pengaruh Diskon Online Shop Melalui Instagram Terhadap Minat Beli Mahasiswa Program Studi Pendidikan Ekonomi Fakultas Tarbiyah Dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau - Nuramaliyah, Nuramaliyah (Journal of Sustainable Education, 2024)
This research aimed at knowing the significant effect of Online shop discounts through instagram on buying interest of economics education students at State Islamic University of Sultan Syarif Kasim Riau. This research were motivated by some students who did not use Instagram to Online shop, students did not know the information about the Online shop discounts on Instagram, students did not know the period of the Online shop discount on Instagram. This research used descriptive quantitative method. The population of this research were 139 students. The samples of this research were 50 students. Questionnaire and documentation techniques were used for collecting the data. Validity, reliability, normality, lite linearity, simple linear regression analysis and hypothesis tests were used for analyzing the data. The results of this research were obtained that robserved = 0.554 and rtable in significant levels 5% (0.554 > 0.235), it means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. If compared that robserved = 0.596 and rtable in significant levels 1% (0.554 > 0.361), it means that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Therefore, there was a significant effect of Online shop discounts through instagram on buying interest of economics education students at State Islamic University of Sultan Syarif Kasim Riau.